An empirical assessment of the effects of the 1994 In Trust Agreements on IRRI germplasm acquisition and distribution - Gotor, Elisabetta; Caracciolo, Francesco; Bioversity International (2010)
A study of the impact of the in-trust agreements demonstrated the importance of a clear legal environment for the genebanks. Requests for repatriation of rice germplasm from the International Rice Research Institute peaked in 1994, during the period of uncertainty. This coincided with a period of decline in acquisitions by the genebank. The signing of the in-trust agreements led to a significant decline in repatriation requests. The analysis suggests that the size of the IRRI rice collection could have continued to decline if it were not for the signing of the in-trust agreements. Results moreover confirm the central role of Bioversity and policy research in the negotiations process. Concepts developed during the ITA negotiations contributed towards subsequent multilateral negotiations that eventually culminated in the International Treaty on Plant Genetic Resources.